Investing in a Wealthy Resource-Based Colonial Economy: International Business in Australia before World War I. Issue 2 (2020) - Ville, Simon; Merrett, David Tolmie
Abstract : The article is a rare investigation into multinational activity in a wealthy resource-based colonial economy toward the end of the first wave of globalization. It challenges the conventional wisdom that multinationals had a limited presence in pre-1914 Australia, where government loans and portfolio investment from Britain into infrastructural and primary industries dominated. Our new database of nearly five hundred foreign firms, from various nations and spread across the host economy, shows a thriving and diverse international business community whose agency mattered for economic development in Australia. Colonial ties, natural resources, stable institutions, and high incomes all attracted foreign firms.